Raport z badania ilościowego polskich migrantów wielokrotnych - Olga Czeranowska (University of Warsaw, Centre of Migration Research (CMR), 2019)
– This report presents the results of quantitative research that was a part of the project "In search of a theory of multiple migration. A quantitative and qualitative study of Polish migrants after 1989" (NCN: Sonata Bis funding scheme). Data was gathered with a web-questionnaire, with respondent-driven sampling. Respondents were adults born in Poland who are currently living abroad and had stayed in at least two foreign countries (including the current one). Our sample is feminized, and persons between 25 and 34 are the biggest age group. Another important characteristic of the sample is the dominance of individuals with tertiary education. While half of the sample had lived in more than two foreign countries, the most mobile group (5 migrations and more) constituted only a small percentage of the sample. Three most common countries of respondents first migrations are Great Britain, Germany and USA. In the moment when they took part in the research, the biggest groups of respondents were living in Great Britain, Germany and the Czech Republic. Most frequent motivations for migration (both for first and current migration) were issues related to work.
Keywords: 330; multiple migration; Polish migrants; RDS